Pendekatan Humanistik dalam Pembelajaran Bahasa Arab Perspektif Kurikulum Berbasis Cinta - Inayah, Inayah; Arifudin, Iis; Hidayat, Ade (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study examines the humanistic approach in Arabic language learning through the perspective of a love-based curriculum as an alternative paradigm that is more holistic, meaningful, and humane. The humanistic approach positions students as subjects with a natural potential to develop optimally, integrating the principles of Western humanistic psychology with Islamic educational values (tarbiyah). This research employed library research methodology using a descriptive-analytical approach. Data and data sources consisted of literature on Arabic language teaching methodology (ṭuruq tadrīs al-lughah al-'arabiyyah), as well as secondary sources including accredited international and national journals, conference proceedings, previous research findings, and scientific articles discussing related themes. Data collection technique used documentation by reading, identifying, classifying, and analyzing relevant literature through purposive sampling based on criteria of relevance, source credibility, and contribution to research concept development. Data analysis employed content analysis with a hermeneutic approach to understand the deep meaning of various concepts studied, involving data reduction, thematic categorization, interpretation through comparison of theoretical perspectives, and source triangulation for validation. The findings indicate that the humanistic approach through a love-based curriculum offers fundamental solutions to Arabic language-learning problems by fostering a supportive psychological environment, reducing language anxiety, increasing intrinsic motivation, and developing communicative competence holistically. This approach not only produces linguistically competent graduates but also individuals with noble character, deep love for the Arabic language, and commitment to lifelong learning.